An observer‐blinded randomized controlled pilot trial comparing localized immersion psoralen–ultraviolet A with localized narrowband ultraviolet B for the treatment of palmar hand eczema3. (14th March 2018) - Brass, D.; Fouweather, T.; Stocken, D.D.; Macdonald, C.; Wilkinson, J.; Lloyd, J.; Farr, P.M.; Reynolds, N.J.; Hampton, P.J.
Summary: Background: Hand eczema is a common inflammatory dermatosis that causes significant patient morbidity. Previous studies comparing psoralen–ultraviolet A (PUVA) with narrowband ultraviolet B (NB‐UVB) have been small, nonrandomized and retrospective. Objectives: To conduct an observer‐blinded randomized controlled pilot study using validated scoring criteria to compare immersion PUVA with NB‐UVB for the treatment of chronic hand eczema unresponsive to topical steroids. Methods: Sixty patients with hand eczema unresponsive to clobetasol propionate 0·05% were randomized to receive either immersion PUVA or NB‐UVB twice weekly for 12 weeks with assessments at intervals of 4 weeks. The primary outcome measure was the proportion of patients achieving 'clear' or 'almost clear' Physician's Global Assessment (PGA) response at 12 weeks. Secondary outcome measures included assessment of the modified Total Lesion and Symptom Score (mTLSS) and the Dermatology Life Quality index (DLQI). Results: In both treatment arms, 23 patients completed the 12‐week assessment for the primary outcome measure. In the PUVA group, five patients achieved 'clear' and eight 'almost clear' [intention‐to‐treat (ITT) response rate 43%]. In the NB‐UVB group, two achieved 'clear' and five 'almost clear' (ITT response rate 23%). For the secondary outcomes, median mTLSS scores were similar between groups at baseline (PUVA 9·5, NB‐UVB 9) and at 12 weeks (PUVA 3, NB‐UVB 4). Changes in DLQI were similar, with improvements in both groups. Conclusions: In this randomized pilot trial recruitment was challenging. After randomization, there were acceptable levels of compliance and safety in each treatment schedule, but lower levels of retention. Using validated scoring systems – PGA, mTLSS and DLQI – as measures of treatment response, the trial demonstrated that both PUVA and NB‐UVB reduced the severity of chronic palmar hand eczema. Abstract : What's already known about this topic? Psoralen–ultraviolet A (PUVA) is widely used for the treatment of topical‐steroid‐resistant hand eczema. Despite the widespread use of narrowband ultraviolet B (NB‐UVB) for whole‐body eczema there have been few investigations of NB‐UVB for hand eczema. Small studies have shown NB‐UVB to be safe, but formal comparison with PUVA by randomized controlled trial has not been performed. What does this study add? This pilot study suggests that both immersion PUVA and NB‐UVB are effective treatments for palmar hand eczema. NB‐UVB appears more likely to cause mild side‐effects such as erythema. NB‐UVB for hand eczema is a safe and reasonable alternative to PUVA. Recruitment of sufficient numbers of patients to a noninferiority study comparing PUVA with NB‐UVB may be challenging. Linked Comment: Oosterhaven. Br J Dermatol 2018;179 :8–9 . Plain language summary available online Respond to this article